Some physicochemical properties of acetaminophen pediatric suspensions formulated with okra gums obtained from different extraction processes as suspending agent - Ikoni, Ogaji (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this work was to evaluate the effect of the extraction process and the potential of okra gum as a suspending agent in pharmaceutical oral formulations containing acetaminophen as a model drug. Clarified mucilage of dried okra was either extracted directly with ethanol 96% (F1) or was first treated with base (F2), acid (F3) or heating in the presence of salt (F4) before extraction with ethanol 96%. The samples were used at 0.5% w/v as suspending agents in acetaminophen acetaminophen suspension to deliver 125 mg/5 mL acetaminophen. A binary mixture of F2 and F4 (1:1) was also used. Similar suspensions of acetaminophen containing either hydroxymethylpropylcellulose (HPMC) or tragacanth gum (TRAGA) were produced. Some physicochemical properties of the formulations were evaluated. The rheological properties of acetaminophen-containing treated okra gums (F2-F5) were generally similar. Changes in viscosity with storage were slower in the F2-F5 formulations as compared with F1. Particle size and particle size distribution were different for all formulations, and hysteresis was a function of time and the suspending agent used.The re-dispersion time of the formulations with treated okra gums was generally shorter than that observed with the untreated okra gum. The use of a binary mixture of F2 and F4 resulted in different physicochemical properties from those of either F2 or F4.The physicochemical properties of the formulations were comparable to those with HPMC and TRAGA. It can thus be concluded that treating okra gum with acid, base or salt impacted better physicochemical properties on an acetaminophen pediatric suspension when they were used as suspending agents.